FASE KETIGA PERKEMBANGAN HADIS - Marhany Malik; Dian Islamiyah (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2023)
This article discusses the development of hadith in the third phase. In this article there are several important things that will become the core of the discussion, namely, the understanding of hadith science, the process of writing and bookkeeping of hadiths, the activities of hadith scholars, the form of compiling hadith books, hadith scholars and the development of hadith books that occurred during the third phase. Therefore, it is necessary to explain these things so as not to cause confusion and misunderstanding in understanding related to the historical development of hadith in the third phase. The study of this problem was carried out by conducting a literature review with a historical approach. So the conclusion is the codification of the traditions of the Prophet. the occurrence of scientific visits conducted by hadith scholars to collect the hadiths of the Prophet. In terms of the systematics of compiling the book in this third phase, there are three typologies of arrangement, namely; al-shahih, al-sunan and musnad.